The Effect of Financial Literacy, Digital Lifestyle, and Peer Influence on the Financial Management of Boarding House Students in Bandar Lampung - Azzahra Nur Yesika; Erna Listyaningsih; Hiro Sejati (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the partial and simultaneous effects of financial literacy, digital lifestyle, and peer influence on the financial management of boarding house students (anak kost) in Bandar Lampung. This study employs a quantitative approach with an explanatory design. The research sample consisted of 100 respondents who are active university students aged 18–25 living in boarding houses in Bandar Lampung, selected using a purposive sampling technique. Primary data collection was conducted through an online closed-ended Likert scale questionnaire, and the collected data were analyzed using multiple linear regression. The results indicate that partially, financial literacy has a positive and significant effect on financial management (significance 0.000 < 0.05). Digital lifestyle also has a positive and significant effect on financial management (significance 0.001 < 0.05). Similarly, peer influence has a positive and significant impact on students' financial management (significance 0.012 < 0.05). Simultaneously, financial literacy, digital lifestyle, and peer influence collectively have a significant effect on the financial management of boarding students, with an influence contribution of 75.8%. In conclusion, good financial management among boarding students is shaped by a combination of adequate financial understanding, wise utilization of digital technology, and a mutually supportive peer environment.